Management of Paediatric Ulcerative Colitis, Part 2: Acute Severe Colitis—An Evidence-based Consensus Guideline From the European Crohn's and Colitis Organization and the European Society of Paediatric Gastroenterology, Hepatology and Nutrition. Issue 2 (August 2018) - Turner, Dan; Ruemmele, Frank M.; Orlanski-Meyer, Esther; Griffiths, Anne M.; de Carpi, Javier Martin; Bronsky, Jiri; Veres, Gabor; Aloi, Marina; Strisciuglio, Caterina; Braegger, Christian P.; Assa, Amit; Romano, Claudio; et al.
ABSTRACT: Background and aim: Acute severe colitis (ASC) is one of the few emergencies in pediatric gastroenterology. Tight monitoring and timely medical and surgical interventions may improve outcomes and minimize morbidity and mortality. We aimed to standardize daily treatment of ASC in children through detailed recommendations and practice points which are based on a systematic review of the literature and consensus of experts. Methods: These guidelines are a joint effort of the European Crohn's and Colitis Organization (ECCO) and the European Society of Paediatric Gastroenterology, Hepatology and Nutrition (ESPGHAN). Fifteen predefined questions were addressed by working subgroups. An iterative consensus process, including 2 face-to-face meetings, was followed by voting of the national representatives of ECCO and all members of the Paediatric Inflammatory Bowel Disease (IBD) Porto group of ESPGHAN (43 voting experts). Results: A total of 24 recommendations and 43 practice points were endorsed with a consensus rate of at least 91% regarding diagnosis, monitoring, and management of ASC in children. A summary flowchart is presented based on daily scoring of the Paediatric Ulcerative Colitis Activity Index. Several topics have been altered since the previous 2011 guidelines and from those published in adults. Discussion: These guidelines standardize the management of ASC in children in an attempt to optimize outcomes of this intensive clinical scenario. Abstract : Supplemental Digital Content is available in the text